Pembekalan Motivasi Kerja Dan Implementasi Pembelajaran Penggunaan Google Drive Sebagai File Cloud Perangkat Desa Jaring Halus - Nur Anzelina Hrp; Rahmat Syaibani; Rodia Afriza; Idzhari Rahman; Elsa Aditya; Nahar Maganda Saragih; Naya Al Farizky (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Advances in information and communication technology at this time become a potential to improve the quality of government activities and agencies both public and private are required to be more creative in managing human resources. human resources. With the increasingly widespread access to the internet, information information is increasingly open to be accessed by everyone. Google Drive is one of the media that can facilitate all the needs of the village head and staff in human resource activities. and staff in human resource activities. Nowadays, staff and village heads must be able to manage files, both personal files and files from other sources (internet). For this reason, it is necessary to understand the management of file sharing and storage. and file storage. There is still limited equipment in the village office and knowledge of information technology among staff and village heads, there is a need for coaching. there is a need for coaching. ICT-based cooperative coaching is currently still done conventionally (off-line). With the implementation of implementation of Google Drive as a file cloud can ensure the performance of staff and village heads is more efficient, making them more adaptive and responsive. more efficient, make staff and village heads more adaptive and responsive, and increase the quality of good work motivation. and improve the quality of good work motivation will also have an impact on efforts toimprove and develop human resources within the village office.